Tri- and Pentacyclic Azaphenothiazine as Pro-Apoptotic Agents in Lung Carcinoma with a Protective Potential to Healthy Cell Lines - Magdalena Skonieczna; Anna Kasprzycka; Małgorzata Jeleń; Beata Morak-Młodawska (Molecules, 2022)
The phenothiazine derivatives, tricyclic 10H-3,6-diazaphenothiazine (DPT-1) and pentacyclic 7-(3′-dimethylaminopropyl)diquinothiazine (DPT-2), have recently been shown to exhibit promising anticancer activities in vitro. In this report, we demonstrated that DPT-1 and DPT-2 could be pro-apoptotic agents in lung carcinoma, the human lung carcinoma A549 and non-small lung carcinoma H1299, in the range of IC50 = 1.52–12.89 µM, with a protective potential to healthy cell lines BEAS-2B and NHDF. The compounds showed higher activity in the range of the tested concentrations and low cytotoxicity in relation to normal healthy cells than doxorubicin, used as the reference drug. The cytostatic potential of DPT-1 and DPT-2 was demonstrated with the use of MTT assay. Cell cycle analysis via flow cytometry using Annexin-V assay showed the pro-apoptotic and pro-necrotic role of the studied diazaphenothiazines in the cell cycle. DPT-1 and DPT-2 initiated a biological response in the investigated cancer models with a different mechanism and at a different rate. Based on these findings, it can be concluded that DPT-1 and DPT-2 have potential as chemotherapeutic agents.